Taking Stock of Carbon Disclosure Research While Looking to the Future: A Systematic Literature Review - Bazhair, Ayman Hassan; Khatib, Saleh F. A.; Al Amosh, Hamzeh (Sustainability, 2022)
Carbon disclosure research has sparked a growing interest due to climate change phenomenon and the impact thereof on the global market in recent years. Despite this trend, there is still a gap in knowledge regarding the role that carbon disclosure plays in the economic activities of corporations. Therefore, the purpose of this study is to systematically review the available literature on corporate carbon reporting by assessing current research trends, theoretical perspectives, and themes discussed in the field. A final sample of 168 studies from the Scopus database that explicitly discussed carbon reporting were included in this investigation. The results indicated an increase in the number of studies, especially in the last five years. In addition, carbon disclosure practices vary between different firm types, sectors, and countries. However, there is a shortage of empirical studies on some contexts that have rarely been considered. Moreover, it was found that the existing literature has only focused on the demographic characteristics of firms as the driving factor of carbon disclosure, while little attention has been paid to the attributes of governance, auditing, top management, and ownership. Nevertheless, there is no academic consensus on some determinants of carbon reporting, including profitability and the effect of the industry. With regard to the reporting quality, there is no evidence that less disclosed information means that reporting is rare in quality. This study provides a comprehensive, systematic analysis of carbon disclosure studies. The implications for future research are also discussed.